Role of Posterodorsal Medial Amygdala Urocortin-3 in Pubertal Timing in Female Mice - Ivanova, Deyana; Li, XiaoFeng; Liu, Yali; McIntyre, Caitlin; Fernandes, Cathy; Lass, Geffen; Kong, Lingsi; O’Byrne, Kevin T. (Frontiers in Endocrinology, 2022)
Post-traumatic stress disorder impedes pubertal development and disrupts pulsatile LH secretion in humans and rodents. The posterodorsal sub-nucleus of the medial amygdala (MePD) is an upstream modulator of the hypothalamic gonadotropin-releasing hormone (GnRH) pulse generator, pubertal timing, as well as emotional processing and anxiety. Psychosocial stress exposure alters neuronal activity within the MePD increasing the expression of Urocortin3 (Ucn3) and its receptor corticotropin-releasing factor type-2 receptor (CRFR2) while enhancing the inhibitory output from the MePD to key hypothalamic reproductive centres. We test the hypothesis that psychosocial stress, processed by the MePD, is relayed to the hypothalamic GnRH pulse generator to delay puberty in female mice. We exposed C57Bl6/J female mice to the predator odor, 2,4,5-Trimethylthiazole (TMT), during pubertal transition and examined the effect on pubertal timing, pre-pubertal LH pulses and anxiety-like behaviour. Subsequently, we virally infected Ucn3-cre-tdTomato female mice with stimulatory DREADDs targeting MePD Ucn3 neurons and determined the effect on pubertal timing and pre-pubertal LH pulse frequency. Exposure to TMT during pubertal development delayed puberty, suppressed pre-pubertal LH pulsatility and enhanced anxiety-like behaviour, while activation of MePD Ucn3 neurons reduced LH pulse frequency and delayed puberty. Early psychosocial stress exposure decreases GnRH pulse generator frequency delaying puberty while inducing anxiety-behaviour in female mice, an effect potentially involving Ucn3 neurons in the MePD.